Nutritional status of pediatric patients in Ramathibodi Hospital using the WHO child growth standard and the Thai growth reference - Jirattikarn Jirawong (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND | 2020. Background: The appropriate assessment of nutritional status in children is an essential aspect of health supervision. Currently, there are two references used for growth assessment in Thailand. The WHO child growth standard, which has been widely used since 2007, and the Thai growth reference developed by the Ministry of Public Health, which has been used since 1998. However, there were very few studies that made a direct comparison between both tools. Objective: To compare the nutritional status of healthy pediatric patients in Ramathibodi Hospital assessed by the World Health Organization (WHO) child growth standard and the Thai growth reference. Materials and Methods: The present study was a cross-sectional study. The data were collected from all pediatric patients registered in the outpatient department (OPD) of Faculty of Medicine, Ramathibodi Hospital between January 2013 and December 2018. All healthy children (aged 0 to 15 years) were included. Exclusion criteria of possibly chronically ill children were defined by those who were 1) visiting subspecialty clinics, 2) OPD and emergency room (ER) visits more than ten times per year, 3) having ICD-10 of chronic conditions, or 4) had been admitted in the hospital during the study. The weight and height or length data were extracted from the Electronic Medical Record system. All data were analyzed by the Stata Statistical Software focusing on age and sex-specific Z-scores, which references the WHO child growth standard and the Thai growth reference. Results: Sixty-two thousand one hundred four OPD visits were divided into 31,662 OPD visits for boys and 30,442 OPD visits for girls. Percent of weight for age and height or length for age more than +2 Z-score of both boys and girls when using the Thai growth reference was greater than that using the WHO child growth standard, especially for children aged 0 to 12 months. The Thai growth reference classified as overweight were approximately 10.26% to 31.12% more than using the WHO child growth standard. There was no difference in classification of height by both standards. Conclusion: There was a difference in classification of nutritional status between the Thai growth reference and the WHO child growth standard.